CLASSIC CARS: THE MOST ICONIC MODELS OF THE 20TH CENTURY - Kanellakis, Christos; Desypris, Nikos (Open Schools Journal for Open Science, 2025)
This report explores the most iconic classic cars of the 20th century, highlighting their design, historical importance, and cultural significance. From American muscle to European elegance, these vehicles represent a rich heritage in automotive history.